British society, 1680-1880 : dynamism, containment, and change - Price, Richard, 1944- (Cambridge University Press, 1999)
A sustained, radical new interpretation of British history in the eighteenth and nineteenth centuries, by a senior social historian confronting and questioning dominant interpretations. Scholars and students will find much of interest in this elegantly written and lucidly organised study.